2003
DOI: 10.1101/gad.1125603
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the transcriptional activator NtrC1: structural studies of the regulatory and AAA+ ATPase domains

Abstract: Transcription by54 RNA polymerase depends on activators that contain ATPase domains of the AAA + class. These activators, which are often response regulators of two-component signal transduction systems, remodel the polymerase so that it can form open complexes at promoters. Here, we report the first crystal structures of the ATPase domain of an activator, the NtrC1 protein from the extreme thermophile Aquifex aeolicus. This domain alone, which is active, crystallized as a ring-shaped heptamer. The protein car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
308
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 183 publications
(319 citation statements)
references
References 60 publications
(79 reference statements)
11
308
0
Order By: Relevance
“…The recent crystal structure of the ADP-bound NtrC1, another bacterial s 54 -dependent EBP, indicates that the GAFTGA motif indeed forms part of a stable loop structure that protrudes from each NtrC1 subunit into the lumen of the central pore of an oligomeric ring of NtrC1 protomers, rather like the iris of a camera. (16) This exciting new high-resolution structure confirms the proposed arrangement of the GAFTGA motif within the PspF model and demonstrates that these sequences are ideally placed to interact with s 54 . However, determining the precise ways in which the s 54 -RNAP and PspF associate for remodelling the closed complexes will require detailed co-complex structural information.…”
Section: )supporting
confidence: 61%
See 2 more Smart Citations
“…The recent crystal structure of the ADP-bound NtrC1, another bacterial s 54 -dependent EBP, indicates that the GAFTGA motif indeed forms part of a stable loop structure that protrudes from each NtrC1 subunit into the lumen of the central pore of an oligomeric ring of NtrC1 protomers, rather like the iris of a camera. (16) This exciting new high-resolution structure confirms the proposed arrangement of the GAFTGA motif within the PspF model and demonstrates that these sequences are ideally placed to interact with s 54 . However, determining the precise ways in which the s 54 -RNAP and PspF associate for remodelling the closed complexes will require detailed co-complex structural information.…”
Section: )supporting
confidence: 61%
“…(11) Characteristically, all AAAþ members have the ability to self-assemble into higher order oligomeric structures, often as hexamers arranged in a ring shape. (13)(14)(15)(16) They also have the conserved functionality of transforming the energy derived from NTP hydrolysis to a mechanical force typically used to remodel protein and protein-nucleic acid complexes. (11,12,17) Sequence alignments have demonstrated that AAAþ proteins share common motifs, namely the AAA minimum consensus, Walker A, Walker B, Sensor I and Sensor II.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ring structures of AAAϩ proteins can be created through the regulated assembly of monomers or dimers, the formation a stable ring upon assembly of the subunits, or the formation of a ring from a single polypeptide chain containing multiple AAAϩ domains (42). Activators of 54 -holoenzyme appear to form ring structures through the regulated assembly of subunits (18). Crystal structures were reported recently for the ADP-bound form of the ATPase domain alone and the ATPase and adjacent regulatory do-mains of Aquifex aeolicus NtrC1, a 54 -dependent activator (18).…”
mentioning
confidence: 99%
“…The LuxO has two separate N-terminal regulatory and C-terminal DNA binding domain where the oligomerization or AAA ? ATPase domain is located between the receiver domain and a helix turn helix (HTH) motif [31,65,66]. The HTH motif are known to recognize enhancer like sequence between 100 and 150 base pairs present in upstream of the promoter of the target genes.…”
Section: Luxomentioning
confidence: 99%